A geospatial evaluation of oil spill impact potential on coastal tourism in the Gulf of Mexico. (March 2018) - Nelson, J.R.; Grubesic, T.H.; Sim, L.; Rose, K.
Highlights: We identify degrees of oiling along the coast line of the Gulf of Mexico. Findings suggest that many areas of tourism activity have small oiling. Approach demonstrates the ability to forecast oil landfall locations. Results enhance understanding oil spill and impact characteristics. Different spill scenarios result in vastly different impacts.